PENAWARAN DAN PERMINTAAN KOMODITAS KACANGKACANGAN DAN UMBI-UMBIAN DI INDONESIA - ARIANI, MEWA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005, 2012)
The food policy is so strong on rice commodity and less noticing other food commodities. The objectives of this paper is to analyze supply and demand of beans and tubers in Indonesia, using secondary data from Center Bureaue of Statistic (CBS). The Results are : 1) economic crisis cause the production of beans and tubers decrease due to the decreasing of planted area. The import of those commodity increase but their volume of export tend to decrease; 2) the economic crisis also induces impact on increasing soybeans and cassava consumption as a result of substitution from animal to vegetables food and from rice to cassava.; 3) food and feed industries development has a positive growth that can be seen from the increasing volume and value of output product from beans and tubers; 4) in the next 10 years, demand of soybeans will be increasing but their production tend to decrease. The demand of cassava is also increasing and the production will be decreasing so it cause negative gap between demand and production in 2006. In anticipating the demand of beans and tubers, especially for soybeans and cassava, Indonesian Agency of Agricultural Research and Development (AARD) has important role to develop farm technology for increasing productivity of both commodity. The AARD has a challenge to invent the high variety of commodity which technically suitable, economically profitable and socially acceptable. On the other hand, Indonesian government should arrange tariff policy in import commodity procedure, especially soybeans, to give protection to the farmer.
Keywords: Demand, Supply, Beans, Tubers